Diagnostic accuracy of midtrimester antenatal ultrasound for multicystic dysplastic kidneys. (3rd October 2017) - Scala, C.; McDonnell, S.; Murphy, F.; Leone Roberti Maggiore, U.; Khalil, A.; Bhide, A.; Thilaganathan, B.; Papageorghiou, A. T.
ABSTRACT: Objectives: To establish the diagnostic accuracy of obstetric ultrasound at a tertiary fetal medicine center in the prenatal detection of unilateral and bilateral multicystic dysplastic kidney (MCDK) in fetuses in which this condition was suspected, and to undertake a systematic review of the relevant literature. Methods: This was a retrospective observational study of all cases referred to a regional tertiary fetal medicine unit due to suspicion of either unilateral or bilateral MCDK between 1997 and 2015. Diagnosis was confirmed by postnatal ultrasound reports or postmortem examination. The accuracy of prenatal ultrasound in the diagnosis of MCDK was calculated. Using a systematic search strategy we also performed a review of the literature regarding the prenatal diagnosis and diagnostic accuracy of MCDK. Results: We included 144 women in our analysis; 37 (25.7%) opted for pregnancy termination (TOP) (due to unilateral MCDK with additional abnormalities, suspected bilateral MCDK or severe obstructive uropathy). Complete pre‐ and postnatal data were available in 126 pregnancies, including 104 livebirths, 19 TOPs with postmortem findings available and three intrauterine fetal deaths. Two infants died shortly after birth (due to known bilateral MCDK or known cranial vault defect). The overall number of cases of MCDK confirmed postnatally was 100; of these, 98 were diagnosed prenatally (true positive), while two were thought to be hydronephrosis prenatally (false negative) and the diagnosis of MCDK was made after birth. In nine cases, the initial antenatal diagnosis of suspected MCDK was revised, either later in pregnancy ( n  = 2) or postnatally ( n  = 7) (false positive). Overall, the diagnostic accuracy in our population for the use of antenatal ultrasound to detect MCDK was 91.3%, while that reported in the existing literature was found to range from 53.3% to 100%. MCDK was isolated in the majority (71%) of cases, while in 29% of cases it was found to be associated with other renal and extrarenal fetal abnormalities. Conclusions: Antenatal ultrasound had a diagnostic accuracy of about 91% in the prediction of postnatal MCDK and can therefore be used to guide antenatal counseling. However, prenatal or postnatal revision of the diagnosis occurred in about 7% of cases and parents should be counseled appropriately. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.